2011
DOI: 10.1093/cvr/cvr127
|View full text |Cite
|
Sign up to set email alerts
|

Molecular determinants of cardiac specification

Abstract: In this review, we report and analyse the molecular factors involved in cardiogenesis from the earliest stages of development, using mainly the chick embryo as a model. The first part of the review demonstrates the areas where cardiogenic cells are located from gastrula stages, analysing a brief summary of the fate map of cardiogenic cells, from the epiblast through to the primitive heart tube. The next part analyses the commitment of pre-cardiac cells in cardiogenesis before, during, and after ingression thro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(23 citation statements)
references
References 118 publications
(118 reference statements)
0
21
0
Order By: Relevance
“…However, the precise spatio-temporal relationship between these two inductive signals during heart development remains rather elusive. It was previously reported (Lopez-Sanchez and Garcia- Martinez, 2011) that Fgf8 and Bmp2 are firstly expressed at the level of the primitive streak, and subsequently on the endoderm adjacent to the precardiac mesoderm (see Supplementary Fig. 1).…”
Section: Resultsmentioning
confidence: 78%
See 1 more Smart Citation
“…However, the precise spatio-temporal relationship between these two inductive signals during heart development remains rather elusive. It was previously reported (Lopez-Sanchez and Garcia- Martinez, 2011) that Fgf8 and Bmp2 are firstly expressed at the level of the primitive streak, and subsequently on the endoderm adjacent to the precardiac mesoderm (see Supplementary Fig. 1).…”
Section: Resultsmentioning
confidence: 78%
“…In this work, a detailed analysis -by means of double ISH -has revealed that Fgf8 is expressed medially in the endoderm underlying FCF, while Bmp2 is expressed laterally, establishing two specific -yet overlapping -areas of expression. Additionally, although Bmp2 expression was initially observed only in the underlying endoderm (Schultheiss et al, 1997), it was further noted (Schlange et al, 2000;Lopez-Sanchez and Garcia-Martinez, 2011) that Bmp2 is also expressed in precardiac mesodermal cells during early cardiac specification. In this sense, it is important to mention that Fgf8 is expressed only in the endoderm in chick development, whereas mouse Fgf8 expression is observed at both endodermal and precardiac mesodermal levels (Crossley and Martin, 1995), as previously described in zebrafish as well (Reifers et al, 2000).…”
Section: Discussionmentioning
confidence: 99%
“…Cranial mesoderm is derived from progenitor cells that activate the bHLH transcription factor MESP1 in the primitive streak, under control of the T-box factor Eomesodermin (Saga et al 2000;Costello et al 2011). The pattern of inductive signals from adjacent endoderm and overlying ectoderm together with inhibitory signals from the embryonic midline and posterior region of the embryo refine the sites in which the cardiomyogenic transcriptional program is first activated (Marvin et al 2001;Harvey 2002;Lopez-Sanchez and Garcia-Martinez 2011). These signals, including bone morphogenetic protein (BMP), fibroblast growth factor (FGF), and WNT signals, in addition to short range signaling including fibronectin mediated cascades, result in the activation of key upstream transcriptional regulators of the cardiac phenotype including genes encoding the transcription factors NKX2-5, GATA4, and TBX5, and chromatin remodeling protein SMARCD3 (BAF60c) (Lopez-Sanchez and Garcia-Martinez 2011; Cheng et al 2013).…”
Section: Cardiac Specification and Early Heart Tube Developmentmentioning
confidence: 99%
“…The process of cardiac lineage specification and differentiation is primarily controlled by activating or inhibitory signals of activin A, bone morphogenetic protein (BMP), Wnt, Notch, and FGF signaling networks, regulating key cardiac transcriptional factors such as Nkx2-5, GATA4, Tbx5, and chromatin remodeling protein SMARCD3 [18e20, 22,24,69,70], which in turn are indispensable for the transcription of the cardiomyocyte contractile apparatus. The commitment of the Bryþ mesodermal progenitors toward a cardiogenic fate requires the inhibition of canonical and activation of noncanonical Wnt signaling [71].…”
Section: Pathways Controlling Specification and Differentiation Of Emmentioning
confidence: 99%